Body Image and Body Dysmorphic Disorder Tendency of Women Social Media Users - Islamiyah, Nurul; Murdiana, Sitti; Ismail, Ismalandari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Body image is a psychological factor that causes body dysmorphic disorder tendencies. Where, individuals feel satisfied or dissatisfied with the shape of the body so that they try to achieve the desired body. The purpose of the study was to determine the relationship between body image and the tendency of body dysmorphic disorder in female social media users. The survey of this study was 202 subjects. The study used quantitative methods using Spearman rho correlation data analysis techniques with a coefficient of -0.469 with p=0.00 (p<0.05). The results show that there is a very significant negative relationship between body image and the tendency of body dysmorphic disorder in female social media users. This means that the lower the body image, the higher the tendency of body dysmorphic disorder and vice versa, the higher the body image, the lower the tendency of body dysmorphic disorder in social media users. So, a female social media user may feel satisfied with herself. However, she can also unconsciously develop an obsession to be better, cover up flaws and continue to change her appearance.Body image merupakan faktor psikologi penyebab terjadinya kecenderungan body dysmorphic disorder. Dimana, individu merasa puas ataupun kurang puas dengan bentuk tubuh sehingga mengusahakan tercapaianya tubuh yang di inginkan. Tujuan penelitian untuk mengetahui hubungan body image dengan kecenderungan body dysmorphic disorder pada perempuan pengguna media sosial. Survei penelitian ini adalah 202 subjek. Penelitian menggunakan metode kuantitatif menggunakan teknik analisis data korelasi Spearman rho dengan hasil koefisien sebesar -0,469 dengan p=0,00 (p<0,05). Hasil menunjukkan terdapat hubungan negatif yang sangat signifikan body image dengan kecenderungan body dysmorphic disorder pada perempuan pengguna media sosial. Hal ini berarti bahwa semakin rendah body image, semakin tinggi kecenderungan body dysmorphic disorder begitupun sebaliknya, semakin tinggi body image, semakin rendah kecenderungan body dysmorphic disorder pada pengguna media sosial. Jadi, perempuan pengguna media sosial bisa saja merasakan kepuasan terhadap dirinya. Tetapi, dia juga bisa tidak sadar mengembangkan obsesi untuk menjadi lebih baik, menutupi kekurangan dan terus mengubah penampilan dirinya.